Tren Pertumbuhan Lembaga Pendidikan Pesantren di Bima Tahun 2001-2012 - Mukhlis Mukhlis (Universitas Islam Negeri Mataram, 2014)
Studies on pesantren growth and development remains urgent. This paper aims to reveal the trend of pesantren growth in Bima (both District of Bima and Municipality of Bima), during 2001 to 2012 which was divided into three four-years, ie 2001-2004, 2005-2008, and 2009- 2012. Utilizing and analyzing data from the Ministry of Religious Affairs of Bima, the authors found that: (1) In the first four-years, 11 new pesantren emerged (growth average 2.75 per year) with a relatively consistent trend. (2) In the second four-years, 21 new pesantren born (average 5.25 per year) with very volatile trend. (3) In the third four-years, 11 new pesantren born (average 2.75 per year) with a fairly volatile trend. (4) Overall, during 2001 to 2012, 43 pesantren born (average 3.58 per year) with a fluctuative growth rate. Pesantren growth reached its peak in 2008 when 10 (23.26%) new pesantren born.